2020
DOI: 10.21203/rs.3.rs-27529/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Transplant of Combined Platelet-rich Fibrin Releasate and Bone Marrow Stem Cells Prevent Bone Loss in Ovariectomized Osteoporotic Mice

Abstract: Background: Osteoporosis is a metabolic bone disorder characterized by deterioration in the quantity and quality of bone tissue, with a consequent increase susceptibility to fracture. Methods: In this study, we sought to determine the efficacy of platelet-rich fibrin releasates (PRFr) in augmenting the therapeutic effects of stem cell-based therapy in treating osteoporotic bone disorder. An osteoporosis mouse model was established through bilateral ovariectomy on 12-week-old female ICR (Institute of Cancer Res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…There was a difference in staining of tibia microstructures in the comparison of (a) OVX and (b) SHAM. During the staining process, the same reaction as in previous studies could be confirmed (Wong et al, 2020). We were also able to acquire a twodimensional (2D) image of a limited location and the bone was found to be made of hard tissue.…”
Section: Analysis Of Axial Axis Of Mouse Tibia Microstructures Using Conventional Methods and Srsupporting
confidence: 68%
“…There was a difference in staining of tibia microstructures in the comparison of (a) OVX and (b) SHAM. During the staining process, the same reaction as in previous studies could be confirmed (Wong et al, 2020). We were also able to acquire a twodimensional (2D) image of a limited location and the bone was found to be made of hard tissue.…”
Section: Analysis Of Axial Axis Of Mouse Tibia Microstructures Using Conventional Methods and Srsupporting
confidence: 68%
“…Elseweidy et al [26] demonstrated that the combination of MSC and the antioxidant resveratrol was more effective in increasing bone mass and improving osteoporosis than treatment alone. Some studies had shown that the combination of plateletrich fibrin releasates (PRFr) and BMSCs [27] or ADSCs 10 Stem Cells International [28] could reduce bone loss in OVX osteoporotic mice. Based on the above findings, we can find that stem cell transplantation holds promise as a potential treatment for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, red i-PRF combined with bone substitute material application may be more effective than the yellow i-PRF [12]. Intervention using the combination of BMSCs and PRFr has more significant results in improving osteogenesis, which served as an understanding for further developing a novel therapeutic strategy in treating osteoporosis [13]. Gold nanoparticles to the advanced PRF and fibrin and platelet byproducts could be new substitute strategies to enhance the osteogenesis capacity of the stem cells [14].…”
Section: The Effect Of Prf In Osteogenesismentioning
confidence: 99%